Análisis y beneficios del uso del concreto ligero con base en esferas de poliestireno en elementos estructurales - Vargas Villegas, Raul Kensel (2024)
The principal objective of this research is to study the use of lightweight concrete based on spheres of polystyrene in structural elements and denote its benefits in the general structure. This investigation will be divided into two main parts. First, specimensare made for compressive resistances of 175 kg/cm2 and 210 kg/cm2 with dry specific weights between 1.8 and 2.0 tons per cubic meter, the specimens are tested at ages of 7,14, 21 and 28 days to observe the evolution of the resistance. On the other hand, for the oldest specimens, find the modulus of elasticity and it compare with the Peruvian code E.060 for lightweight concrete. Then, in accordance with the norm ASTM C78, the modulus of rupture of 2 specimens applying loads in the middle thirds are calculated. To end, a cyclic load test is performed on a thin wall of 2000 mm long, 2400 mm high and 10 mm thick and its behavior is analyzed, comparing it with other wall of conventional concrete and similar dimensions. On the second part, with the data obtained, a structural model was prepared for a building with lightweight concrete, and the maximum forces on the base of the buildings were obtained. The results are compared with the building modelled with normal-weight concrete and the design of one of themost requested elements is verified. In addition, in the case of the foundation, the settlements and pressures in the ground are reduced and, consequently, the dimensions of the foundations can be reduced. The results indicate that element can get specific weights less than standard concrete and to get resistances of 175 kg/cm2 and 210 kg/cm2 , the resistance of concrete indicate early evolution in 7 days of approximately 85 percent of the request strength and then presents a 5 percent rise every 7 days. Regarding the modulus of elasticity of the new concrete, it gets a reduction of the 10 percent for the concrete 175 kg/cm2 and reduction for the 15 percent for the concrete 210 kg/cm2 . In the structural design and the reinforcement in a higher load element, it gets a final reduction of steel of 20 percent. Finally, the total weight of the edification was reduced to 80 percent and it is obtained smaller efforts and settlements in the ground.